2008
DOI: 10.1242/jeb.012344
|View full text |Cite
|
Sign up to set email alerts
|

Maternal antibodies reduce costs of an immune response during development

Abstract: SUMMARYYoung vertebrates are dependent primarily on innate immunity and maternally derived antibodies for immune defense. This reliance on innate immunity and the associated inflammatory response often leads to reduced growth rates after antigenic challenge. However, if offspring have maternal antibodies that recognize an antigen, these antibodies should block stimulation of the inflammatory response and reduce growth suppression. To determine whether maternal and/or offspring antigen exposure affect antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
120
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 39 publications
(53 reference statements)
2
120
2
Order By: Relevance
“…This suggests that specific antibody play an important role in fish protection against pathogenic infection. Maternal antibody from the broodstock fish can reduce the risk of mortality rate during the development of fry fish (Grindstaff, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that specific antibody play an important role in fish protection against pathogenic infection. Maternal antibody from the broodstock fish can reduce the risk of mortality rate during the development of fry fish (Grindstaff, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For now, it is not clear whether these elevated antibody concentrations reflect higher maternal antibody transfer, enhanced activity of offspring's own immune system or a combination of both. In Japanese quail, maternal antibodies decline between 6 and 11days post-hatching, and thus the synthesis of endogenous antibodies seems to be independently active only after this age (Grindstaff, 2008). The maternal antibodies persist in the circulation of quail chicks during the first 30days of life (Grindstaff, 2010), and over this period they can provide passive protection against pathogenic agents the mother encountered during her prior life (Brambell, 1970), prime the humoral immune response (Gasparini et al, 2006;Reid et al, 2006) and reduce the costs of antigen challenges associated with growth suppression (Grindstaff, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we measured basal levels of non-specific antibodies (IgY) in the circulation of chicks. These immunoglobulins may be of both maternal and endogenous origin because maternal antibodies pass through the yolk into the embryo (Brambell, 1970) and endogenous IgY-bearing cells have been detected during the embryonic development (Kincade and Cooper, 1971), although endogenous synthesis of antibodies begins to dominate after 2weeks of age (Watanabe and Nagayama, 1979;Grindstaff, 2008). Artificial selection for yolk T concentrations has proved a heritable variation of yolk hormone transfer accounting for nearly half of its total phenotypic variance (Okuliarova et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have demonstrated in birds that an immune challenge during development was responsible for a reduction in the growth rate [25,26], which is known to influence the fitness of nestlings [27]. However, those studies have mostly focused on innate immune mechanisms, and the potential role of the transfer of maternal antibodies as a mechanism favouring chick growth in the face of parasitic challenge has often been neglected (but see [28]). This is perhaps because experimentally assessing such a role requires a specific challenge of mothers before breeding and the monitoring of the dynamics of specific maternal antibodies in offspring via repeated sampling during the subsequent rearing period.…”
Section: Introductionmentioning
confidence: 99%